Hallmarks of Cancers: Primary Antibody Deficiency Versus Other Inborn Errors of Immunity - Abolhassani, Hassan; Wang, Yating; Hammarström, Lennart; Pan-Hammarström, Qiang (Frontiers in Immunology, 2021)
Inborn Errors of Immunity (IEI) comprise more than 450 inherited diseases, from which, selected patients manifest a frequent and early incidence of malignancies mainly lymphoma and leukemia. Primary antibody deficiency (PAD) is the most common form of IEI with the highest proportion of malignant cases. In this review we aimed to compare the oncologic hallmarks and the molecular defects underlying PAD with other IEI entities to dissect the impact of avoiding immune destruction, genome instability and mutation, enabling replicative immortality, tumor-promoting inflammation, resisting cell death, sustaining proliferative signaling, evading growth suppressors, deregulating cellular energetics, inducing angiogenesis, and activating invasion and metastasis in these group of patients. Moreover, some of the most promising approaches that could be clinically tested both in PAD and IEI patients were discussed.